Pengaruh Self Efficacy, Motivasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. PLN Puruk Cahu Kabupaten Murung Raya - Jose Priska; Emy Rahmawati; Setio Utomo (JURNAL BISNIS DAN PEMBANGUNAN, 2020)
In order to achieve satisfactory performance, professional capabilities are needed to achieve this through several stages or conditions. Formal education is still inadequate to achieve professional capabilities. For this reason, HR capabilities of employees must be empowered through training, education and development. HR management according can be interpreted as utilizing human resources within the organization, which is carried out through the functions of human resource planning, recruitment and selection, human resource development, career planning and development, provision of compensation and welfare, occupational safety and health, and industrial relations.This study aims to examine the influence Self Efficacy (X1), Motivation (X2) and Job Satisfaction (X3) towards Employee Performance (Y) PT. PLN Puruk Cahu well Murung Kingdom's e waypartially or simultaneously. Samples were taken as many as 56 employees by using a saturated sampling technique. Data collection uses a questionnaire while the data analyst is using Multiple LinearRegression Analysis through the SPSS version 23 program.The test results prove that Self Efficacy has a significant effect on Partial Employee Performance with a magnitude of 1.9 % including the weak category, Motivation has a significant effect on Employee Performance partially with an influence of 53 % including the category is quite strong , Job Satisfaction has a significant effect on Employee Performance partially with a large effect of 73.8 % including verycategories strong while simultaneously Self Efficacy Leadership , Motivation and Job Satisfaction have a significant effect on Employee Performance with a large influence of 37.5 % including categories weakwhile the remaining 62.5 % is influenced by other variables.Keywords: Self Efficacy, Motivation, Job Satisfaction and Employee Performance